Cooperation in the Classroom : Experimenting with Research Joint Ventures - Michelle S. Goeree; Jeroen Hinloopen (Claremont McKenna College, Department of Economics, 2004)
This paper describes a classroom exercise that illustrates the investment incentives facing firms when technological spillovers are present. The game involves two stages in which student "sellers" first make investment decisions then production decisions. The classroom game can be used to motivate discussions of research joint ventures, the free-rider problem, collusion, and antitrust policy regarding research and development.
Keywords: 330; classroom games; research and development; research joint ventures; technological spillovers; Forschung; Forschungskooperation; Betriebliche Investitionspolitik; Spillover-Effekt; Spieltheorie; Experiment